Social identity and support for defunding the police in the aftermath of George Floyd's murder. (June 2023) - Jackson, Jonathan; Fine, Adam; Bradford, Ben; Trinkner, Rick
In the spring and summer of 2020, police in the United States killed Breonna Taylor, George Floyd, and other unarmed people of color. In one of the largest social movements in the nation's history, thousands engaged in public protests and called to defund or abolish the police. Debate about police racism and the need for reform intensified, with public opinion polls showing how polarized public attitudes were along traditional political lines. Analyzing data from a cross-sectional quota sample survey of 1, 500 U.S. residents conducted in summer 2020, our findings confirmed the proposition that opposition and support for defunding the police was related to not only political views and superordinate identification with the group that the police prototypically represent, but also polarized intergroup identification with the police and the Black Lives Matter movement, as well as people's perceptions of police procedural justice and systemic racism.